2019
DOI: 10.15537/smj.2019.5.23777
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of computed tomography and ultrasound for the prediction of acute appendicitis at King Fahad Specialist Hospital in Buraidah, Saudi Arabia

Abstract: Objectives: To determine the sensitivity and specificity of computed tomography (CT) and ultrasound (US) in predicting acute appendicitis in relation to histopathology reports at King Fahad Specialist Hospital in Buraidah, Saudi Arabia. Methods: A retrospective cohort study included 500 medical records of patients diagnosed with acute appendicitis upon admission to King Fahad Specialist Hospital, Buraidah, Saudi Arabia, between January 2015 and January 2017. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Previous studies have shown that because the ED is a critical staging area for critically ill patients, developing more efficient tools to avoid overcrowding and increase the efficiency of the use of healthcare resources in the ED and ultimately improve the quality of care and health outcomes for ED patients [48][49][50]. The prediction model developed in our study for adults and pediatric ED patients with diagnosed appendicitis is consistent with the goal of establishing a better decision system in ED [51,52].…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have shown that because the ED is a critical staging area for critically ill patients, developing more efficient tools to avoid overcrowding and increase the efficiency of the use of healthcare resources in the ED and ultimately improve the quality of care and health outcomes for ED patients [48][49][50]. The prediction model developed in our study for adults and pediatric ED patients with diagnosed appendicitis is consistent with the goal of establishing a better decision system in ED [51,52].…”
Section: Discussionsupporting
confidence: 75%
“…Meanwhile, the respective values for CT imaging were 95%, 94%, 95%, and 99% [16]. Consequently, Alshebromi and co-workers (2019) reported that US imaging has a sensitivity of 37.0% and specificity of 100.0% while CT imaging has 86.0% and 16.7%, respectively [8]. Reich and co-workers (2011) also compared US and CT imaging in terms of sensitivity and PPV in which results revealed that CT had better sensitivity and PPV of both 100% compared to that of US with sensitivity and PPV of 68.4% and 94.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, CT has been significant in decreasing the percentage of unnecessary appendectomies and was accepted as the standard for the evaluation of patients with suspected AA. Lastly, MRI has shown a high accuracy rate in AA detection and usefulness during the inapplicability of radiation, such as for pregnant women and young patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Wu et al [ 31 ] also chose to include patients who did not undergo surgical intervention and used CT imaging to aid in diagnosis. The issue with this is that CT scanning for acute appendicitis has been shown to have a sensitivity of roughly 80-90% [ 36 ]. Therefore, there is the concern of potential misdiagnoses which could skew results.…”
Section: Reviewmentioning
confidence: 99%